Pengaruh Restaurant Atmosphre Terhadap Repurchase Intention di Situ Party Kota Padang - Yuricha, Stephanie Vivian; Fiza, Adek Kurnia (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
This study aims to explore the relationship between restaurant atmosphere and repurchase intention. It employs a quantitative descriptive approach using purposive non-probability sampling, with a sample of 80 respondents. Data was collected through questionnaires distributed via Google Form, utilizing a Likert scale to assess the impact of restaurant atmosphere on repurchase intention at Situ Party, Padang City. The questionnaire has been tested for validity and reliability. Data analysis was carried out using SPSS version 20.00. The average value of 4.24 for the restaurant atmosphere variable in the excellent category and 4.15 for the repurchase intention variable, shows that the research findings place these variables in the good category. The restaurant atmosphere variable has a considerable impact on repurchase intention, as indicated by the estimated F value of 191.941 with Sig 0.000 < 0.05 from the restaurant atmosphere value (X). Additionally, the Adjusted R Square value of 0.711 was found, indicating that 71.1% of the influence on the repurchase intention variable (Y) came from the restaurant atmosphere variable (X), with the remaining 28.9% coming from other sources.